ANALISIS GERAK TARI ALANG BABEGA DI SANGGAR TARI ALANG BABEGA KOTA PADANG - Reva Halwa Soferry; Asriati, Afifah (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study aims to reveal, describe, and analyze the Alang Babega Dance Movement at the Alang Babega Dance Studio in Padang City. The type of research used is qualitative with a descriptive analytical approach. The research instrument is the researcher himself who is assisted by supporting instruments such as stationery, mobile phones, and documentation. Data collection techniques are carried out through observation, interviews, and documentation, while data analysis is carried out through data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that the Alang Babega Dance is a creative dance work originating from the Minangkabau pencak silat (silek) technique created by Gusmiati Suid and preserved at the Alang Babega Dance Studio, with 12 types of movements. This dance is analyzed through aspects of space, time, and energy. In the spatial aspect, the line elements include curved, straight, diagonal, and zigzag lines with a dominance of zigzag lines that give a dynamic impression, the volume includes medium and large with a dominance of medium volume, the direction of facing includes front, side, and back with a dominance of the front direction, the level includes low, medium, and high with a dominance of medium level, and the focus of view includes front, side, bottom, and back with a dominant tendency towards the front. In the time aspect, tempo and rhythm include slow, medium, and fast with a dominance of medium tempo and rhythm that gives the impression of stable movement. In the energy aspect, the intensity includes medium and strong with a dominance of medium intensity, the dominant pressure of movement is strong, and the quality of movement tends to be strong. Thus, the movements of the Alang Babega Dance have a firm, energetic, agile, and sturdy character that represents the theme of the dance, namely the image of an eagle that moves agilely and dynamically (babega) combined with the basic movements of Minangkabau silek. This character is reflected through the processing of elements of space, time, and energy that are interrelated in every variety of movement, thus presenting a dynamic, alert, strong, and free impression as the character of an eagle. The Alang Babega Dance Studio plays an important role in maintaining the sustainability, preservation, and inheritance of the Alang Babega Dance to the younger generation as part of the Minangkabau cultural identity.